2021
DOI: 10.3390/pharmacy9030129
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Community Pharmacy Take Home Naloxone Dispensing during COVID-19: The Impact of One Public Health Crisis on Another

Abstract: A recent report found that the number of opioid-related deaths in Ontario in the first 15 weeks of the COVID-19 pandemic was 38.2% higher than in the 15 weeks before the pandemic. Our study sought to determine if pharmacy professionals self-reported an increase or decrease in naloxone provision due to the pandemic and to identify adjustments made by pharmacy professionals to dispense naloxone during the pandemic. A total of 231 Ontario community pharmacy professionals completed an online survey. Pharmacy profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…When a naloxone kit is dispensed, a study examining pharmacy dispensing data found that the most common reason for dispensing naloxone was the patient's request, and 89.5% of patients indicated that it was their first naloxone kit [26]. A survey examining the dispensing habits of pharmacists during the COVID-19 pandemic found that one of the main barriers for not dispensing naloxone during the pandemic was the lack of patients asking for a naloxone kit [30]. The survey also found that the pharmacists that were proactively offering kits and making adaptations to offer naloxone kits were doing so over the phone or by delivery, to work around less face-to-face interactions between the pharmacists and patients during the COVID-19 pandemic [30].…”
Section: Pharmacy-based Take-home Naloxone Programsmentioning
confidence: 99%
See 4 more Smart Citations
“…When a naloxone kit is dispensed, a study examining pharmacy dispensing data found that the most common reason for dispensing naloxone was the patient's request, and 89.5% of patients indicated that it was their first naloxone kit [26]. A survey examining the dispensing habits of pharmacists during the COVID-19 pandemic found that one of the main barriers for not dispensing naloxone during the pandemic was the lack of patients asking for a naloxone kit [30]. The survey also found that the pharmacists that were proactively offering kits and making adaptations to offer naloxone kits were doing so over the phone or by delivery, to work around less face-to-face interactions between the pharmacists and patients during the COVID-19 pandemic [30].…”
Section: Pharmacy-based Take-home Naloxone Programsmentioning
confidence: 99%
“…A survey examining the dispensing habits of pharmacists during the COVID-19 pandemic found that one of the main barriers for not dispensing naloxone during the pandemic was the lack of patients asking for a naloxone kit [30]. The survey also found that the pharmacists that were proactively offering kits and making adaptations to offer naloxone kits were doing so over the phone or by delivery, to work around less face-to-face interactions between the pharmacists and patients during the COVID-19 pandemic [30]. Therefore, although many patients are not benefiting from the THN program and many pharmacists are not proactively offering naloxone, there is a need for increased and equitable naloxone distribution through community pharmacy THN programs and there are new and innovative approaches to better THN dispensing.…”
Section: Pharmacy-based Take-home Naloxone Programsmentioning
confidence: 99%
See 3 more Smart Citations